2014
DOI: 10.1254/jphs.14013fp
|View full text |Cite
|
Sign up to set email alerts
|

Cyclovirobuxine D Induces Autophagy-Associated Cell Death via the Akt/mTOR Pathway in MCF-7 Human Breast Cancer Cells

Abstract: Abstract. Autophagy is a highly regulated and multi-step biological process that serves to remove damaged cytoplasmic components and organelles. It has been suggested that the activation of autophagy may be a promising therapeutic strategy for cancer treatment by triggering cell death. In this study, we reported that cyclovirobuxine D (CVB-D), an alkaloid component in a traditional Chinese herb, could induce autophagy in the MCF-7 human breast cancer cell line. CVB-D inhibited the viability of MCF-7 cells in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 38 publications
1
45
0
1
Order By: Relevance
“…Mollugin, a bioactive phytochemical isolated from Rubia cordifolia L ., exhibited anticancer activity against various cancer cells [246]. Further experiments demonstrated that PI3K/AKT/mTOR/ p70RS6K and ERK signaling pathways participated in mollugin-induced autophagy and apoptosis [247]. Cyclovirobuxine D (CVB-D) could induce autophagy in the MCF-7 human breast cancer cell line evidenced by accumulation of autophagosomes and elevated LC3B fluorescent puncta, as well as increased LC3B-I-to-LC3B-II conversion, and the expression of ATG5, as described in [247].…”
Section: Anticancer Natural Compounds and Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Mollugin, a bioactive phytochemical isolated from Rubia cordifolia L ., exhibited anticancer activity against various cancer cells [246]. Further experiments demonstrated that PI3K/AKT/mTOR/ p70RS6K and ERK signaling pathways participated in mollugin-induced autophagy and apoptosis [247]. Cyclovirobuxine D (CVB-D) could induce autophagy in the MCF-7 human breast cancer cell line evidenced by accumulation of autophagosomes and elevated LC3B fluorescent puncta, as well as increased LC3B-I-to-LC3B-II conversion, and the expression of ATG5, as described in [247].…”
Section: Anticancer Natural Compounds and Autophagymentioning
confidence: 99%
“…Further experiments demonstrated that PI3K/AKT/mTOR/ p70RS6K and ERK signaling pathways participated in mollugin-induced autophagy and apoptosis [247]. Cyclovirobuxine D (CVB-D) could induce autophagy in the MCF-7 human breast cancer cell line evidenced by accumulation of autophagosomes and elevated LC3B fluorescent puncta, as well as increased LC3B-I-to-LC3B-II conversion, and the expression of ATG5, as described in [247]. CVB-D-induced autophagy and decrease in cell viability could be blocked by 3-MA [247].…”
Section: Anticancer Natural Compounds and Autophagymentioning
confidence: 99%
“…40 The intensity of protein bands was measured by using the Lab Works software (Bio-Rad, Berkeley, CA). Primary antibodies against α-tubulin (diluted 1:5000) were from Sigma-Aldrich (St Louis, MO).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Natural products such as cyclovirobuxine D (CVB-D), an alkaloid component isolated from the roots of Buxus microphylla var. Sinica, are often used as direct or indirect sources to enhance the efficacy of chemotherapy or ameliorate its side effects [67]. A recent study reported carnosol, a naturally occurring polyphenol, being an inducer of ROS-mediated Beclin-1-independent autophagy and apoptosis in triple negative MDA-MB-231 cell line [68].…”
Section: Anticancer Therapies Correlated With Autophagymentioning
confidence: 99%